The Change in the Legitimacy of Sarbedaran Government with the Emphasis on the Role of Shiism and Sufism - mohammad reza roozbahani (تاریخ اسلام)
After the death of Ilkhan Abu Saeed (736 After Hijrah) and the rise of Timor Gourkani (807 After Hijrah) excluding the ones left from changiz dynasty and the local governors, we are observant of newfound governments that develop their organization by taking advantage of time conditions. Sarbedaran in the West of Khorasan (783 After Hijrah), Sadat e- Mazandaran (794 After Hijrah), Sadat e – Gilan (722 After Hijrah), Karkia in Lahijan (1060 After Hijrah) are considered as the governments with mystic tendencies. Among these governments, the role of Sarbedaran e- Khorasan is of great significance due to its vast territory and simultaneous reliance on Shiism and Sufism. Through the descriptive-analytical method, this article has endeavored to analyze the reason of this government’s not achieving a united paradigm to be agreed upon by different groups and to describe the efforts of Sarbedari government towards achieving the legitimacy and presenting a new paradigmfor providing this legitimacy. It seems that the main elements of this failure are the lack of specific political theory in Sarbedari group and the radical idealism of Sheikhian group as well as the complicated political conditions provided particularly due to the appearance of Timor. In some way, the delayed efforts of Khajeh Ali Mo’ayyad in regard with the invitation of Mohammad e- Makki, Shahid Awwal (786 After Hijrah) for founding a religious government and consequently achieving a basis for a new legitimacy could not provide any success for Sarbedari government